<span>(6y3 + 17y − 3) − (4y3 − 11y + 9)
</span>= 6y3 + 17y − 3 − 4y3 + 11y - 9
= 2y3 + 28y - 12
Answer:
12
Step-by-step explanation:
When you a coin flips there are 2 possible outcomes which are either heads, or tailer, when you roll a die there are six outcomes, one to six. Putting these together means you have a total of 2×6=12 outcomes
Divide 18 to both sides and you get -12
Answer:
60
Step-by-step explanation:
Substitute 50 for y in the formula
5x+10y=800
5x+10*50=800
5x+500=800
5x=800-500
5x=300
x=300/5
x=60
Answer:
x=52
Step-by-step explanation: